PRINCIPAL SUPERVISION, WORK DISCIPLINE, AND PEDAGOGICAL COMPETENCE - Sumirah Sumirah (International Journal of Southeast Asia, 2020)
The objectives of this research is to examine the correlation between independent variables such as: principal supervision, work discipline, and pedagogical competence with an dependent variable, Work Quality. The research was conducted on 284 Teacher’s Junior high school who were selected by propotional random sampling in Jambi City; meanwhile the hypothesis test was conducted on 0.05 significance level. This research was conducted by using sequential explanatory mixed methods that prioritize research with quantitative methods and followed by qualitative methods to obtain the results of a significant and comprehensive. The quantitative research concludes that: (1) there is a positive and significant correlation (r = 0.4621, p <0.01) between principal supervision with the work quality, coefficient of determination 0.2127 (r2 = 21.27%) with the regression equation Y = 83.539 + 0,450X1, (2) there is a positive and significant correlation (r = 0.4834, p <0.01) between work discipline with the work quality, coefficient of determination 0.2337 (r2 = 23.37% ) with the regression equation Y = 91.901 + 0,427X2, (3) there is a positive and significant correlation (r= 0.5082, p <0.01), coefficient of determination 0.2583 (r2 = 25.83%) between pedagogical competence with the work quality with the regression equation Y = 91.901 + 0,427X3, (4) there is a positive and significant correlation (r = 0.5815, p <0.01) between principal supervision and discipline of work together with the work quality, coefficient determination 0.3381 (r2 = 33.81%) with a regression equation y = 43.63 + 0,403X1 + 0,388X2, (5) there is a positive and significant correlation (r = 0.5762, p <0.01) between principal supervision and pedagogical competence together with the work quality, coefficient of determination 0.3320 (r2 = 33.20%) with a regression equation y = 48.18 + 0,333X1 + 1,646X3, (6) there is a positive and significant relationship ( r = 0.6188, p <0.01) between discipline of work and pedagogical competence together with the work quality, coefficient of determination 0.3829 (r2 = 38.29%) with a regression equation y = 32.95 + 0.413 X2 + 1,953X3, (7) there is a positive and significant correlation (r = 0.7171, p <0.01) between principal supervision, discipline of work and pedagogical competence with the work quality, determination coefficient 0.5143 (r2 = 51.43%) with a regression equation Y = 7.373 + 0,286X1 + 0,388X2 + 1,643X3.